Obsidian and mafic volcanic glasses from the Philippines and Vietnam found in the Paris Museum Australasian tektite collection. (1st June 2022) - Rochette, P.; Bezaeva, N. S.; Beck, P.; Debaille, V.; Folco, L.; Gattacceca, J.; Gounelle, M.; Masotta, M.
Abstract: During the systematic magnetic susceptibility survey of the Paris Museum Australasian tektite collection, we identified three previously overlooked occurrences of volcanic glass that resembles tektites, based on anomalous magnetic properties, high water content, the presence of microcrystals, and anomalous chemical composition. These occurrences are from the Phu Yen province in south‐central Vietnam (two rhyolitic glass fragments) and from the Philippines: one from northern Luzon Island (a basaltic rounded etched glass), one from Santa Mesa near Manilla (a dozen small rounded rhyolitic gravels). The two occurrences in the Philippines are quite similar to previously described volcanic glasses from the nearby Pagudpod and Nagcarlan localities, respectively. The rhyolitic glass specimens from the Phu Yen province are the first documentation of a geological occurrence of obsidian in Vietnam. This work is a warning note that glass samples with anomalous properties found among tektite collections may correspond to volcanic pseudotektites instead of real tektites with anomalous composition. The basaltic glass sample from the Philippines locally shows microcrystalline quench textures previously unknown in natural samples. These findings may also be of interest for archeologists involved in glass artifacts sourcing.